Design and Development on Intelligent Layout System of Stamping Blanks - Fangjuan Li (Institute of Advanced Engineering and Science, 2012)
The optimal layout of stamping blanks is a complicated problem under the control of multi-circumstances, and it cannot be best solved by any single algorithm. In order to solve this problem, the paper proposed a new kind of algorithm combining CHNN and genetic algorithm. It set up models for irregular parts, and these irregular parts were processed by using the surrounding rectangle methods and graphic composition. The paper used AutoCAD as a develop studio, and discussed CHNN and its mapping to layout and optimize the weight of CHNN by genetic algorithm. The kernel program adopted VB program language and developed the intelligent layout system. With the input of layout parts graphics and layout parameter, the system preprocessed graphics and gave layout results automatically. Sample analysis showed the results that the system had good man-machine interfaces, interactive features, high speed and quality retention of solution. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1601